Reproductive characteristics of malabar blood snapper \(Lutjanus malabaricus\) (Bloch &Schneider, 1801) in coastal marine zone of Nghe An and Ha Tinh provinces, Vietnam - Hai Yen, Dinh Thi; Lam, Hoang Ngoc; Ha, Vo Thi; F.V., Lishchenko; Luc, Nguyen Van; Thuy, Nguyen Thi; Duc Hieu, Nguyen Trinh; Tuan, Hoang Anh (Academia Journal of Biology, 2022)
Malabar blood snapper Lutjanus malabaricus (Bloch & Schneider, 1801) inhabits in coastal marine waters of Nghe An and Ha Tinh provinces, Vietnam. An investigation of the reproductive characteristics of Lutjanus malabaricus in the coastal marine waters of Nghe An and Ha Tinh provinces was undertaken between June 2020 and May 2021. The spawning season of L. malabaricus occurred throughout the year, fish were in the ripe or spawning condition in most months; but spawning peaks from late March/April and August. Females matured at a smaller size than males, with total length (TL) at first maturity being 280–330 mm for males and 230–280 mm for females. The sex ratios of 365 individuals were approximately 1/1, and the total ratio G/W was approximately 0.08−5.65% with a mean of 0.32%. The highest GSI mean value in males was 0.77 (stage IV in July) and the lowest mean value 0.03−0.11 was recorded during stages I and II in November and December. Females had the highest mean value of 1.22−1.41 (stage IV in May) and the lowest mean value of 0.07 during stages I and II in January, and 0.20 at stages I and II in October. These show that fish (L. malabaricus) were ripe or spawning from March and August in the studied waters. The first maturity size was 280−330 mm for males and 230–280 mm for females. Absolute fecundity (Fa) ranged from 24.000 to 769.000 (the mean value 112.000) ova per ovaries for L. malabaricus. In the main spawning period, high gonadal index values were found around the time of the last quarter to the first quarter moon for each month from late March or early April to August. It is suggested that L. malabaricus is a lunar-synchronized spanner in the studied waters.